Accounting Treatments for Cryptocurrencies in Malaysia: The Hierarchical Component Model Approach - Angeline, Yap Kiew Heong; Chin, Wong Siew; Melissa, Teoh Teng Tenk; Saleh, Zakiah (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study examines the influences of technological factors, risks and regulatory framework on the accounting treatments for cryptocurrency in Malaysia. Design/Methodology/Approach: This study employs a structured questionnaire to solicit data about the accounting treatments for cryptocurrency. Data were collected from 391 accounting and finance professionals and analysed using partial least squares structural equation modelling (PLS-SEM). Research findings: The results of this study show that technological factors, risks and regulatory frameworks are positively associated with the accounting treatments for cryptocurrency. Theoretical contribution/Originality: This study has expanded the existing literature by focusing on the accounting treatments forcryptocurrency using the accounting conceptual framework as the theoretical argument. Practitioner/Policy implication: The findings imply that audit, tax and accounting professionals need to address the valuation and reporting of different classes and types of cryptocurrencies as their usage continue to rise. The core competencies of these professions are being disrupted by these changes; hence, these professions need to evolve and work with strategic partners/technology experts to offer cryptocurrency related advisory services. Research limitation/Implications: The researchers consider three factors namely technological, risks and regulatory frameworks that influence the accounting treatments for cryptocurrency. Future researchers may consider working with industry leaders to develop objective guidelines for cryptocurrencies, using comparative analysis of alternative accounting treatments to examine how this impacts financial results. Keywords: Digital Currency, Cryptocurrency, Accounting, Malaysia, Blockchain Technology JEL Classification: E42, G28, M41